Leslie M. Shaw correspondence - Shaw, Leslie M. (Leslie Mortier), 1848-1932.
Typewritten signed and annotated draft of a letter from Shaw to Harvey Ingham, editor of the Des Moines Register and Leader, concerning an editorial in which Shaw claims he was misquoted.
U.S. secretary of the treasury, lawyer, banker, governor of Iowa, and lecturer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Ingham, Harvey, -- 1858-1949 -- Correspondence; Des Moines register and leader; Iowa -- Politics and government; Bankers; Cabinet officers, U.S.; Governors -- Iowa; Lawyers; Lecturers